2022
DOI: 10.3389/fneur.2022.875370
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Case of VV1 Creutzfeldt–Jakob Disease Subtype: Case Report

Abstract: Creutzfeldt–Jakob disease (CJD) is a rare form of rapidly progressive, neurodegenerative disease that results from the misfolding and accumulation of an aberrant, disease-associated prion protein (PrPD). CJD affects 1–1.5 cases per million per year with the sporadic-type accounting for an estimated 85% of these cases. Sporadic CJD (sCJD) is further subdivided into five subtypes based on genetic polymorphisms; the rarest subtype, sCJDVV1, occurs at a rate of 1 case per one-hundredth million population per year.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Different subtypes have different clinical and neuropathological features, as well as survival times and test results ( 8 , 40 , 41 ). The sensitivity of RT-QuIC for detecting MM1 and VV2 is high (96.3%) but can be negative for MM2 and VV1 subtypes ( 33 , 42 ). Younes et al reported that MM1, MV1, and VV2 are related to short duration/fast progression, while MV2, VV1, and MM2 are associated with long duration/slow progression ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different subtypes have different clinical and neuropathological features, as well as survival times and test results ( 8 , 40 , 41 ). The sensitivity of RT-QuIC for detecting MM1 and VV2 is high (96.3%) but can be negative for MM2 and VV1 subtypes ( 33 , 42 ). Younes et al reported that MM1, MV1, and VV2 are related to short duration/fast progression, while MV2, VV1, and MM2 are associated with long duration/slow progression ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“… 57 , 58 The other syndromic neurodegenerative diagnoses encountered in our study have less commonly, or have not been previously, reported to correlate with prosopagnosia including Alzheimer’s disease dementia, 30 , 59 , 60 dementia with Lewy bodies, 61 corticobasal syndrome, behavioural-variant frontotemporal dementia, 62 logopenic progressive aphasia and Creutzfeldt–Jakob disease. 63 This may be because these neurodegenerative diseases tend to target the left hemisphere, frontal lobes or dorsal stream of the occipito-parietal cortex. Hence, the ventral right occipito-temporal cortex is typically spared in these degenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the largest to-date retrospective population study of definitive sCJD cases demonstrated that IQ detected 80% of cases not detectable by PQ [ 8 ]. The study also evaluated IQ sensitivity for different sCJD subtypes and found it to be more sensitive for detection of rare disease subtypes, including VV1 (Parchi’s classification [ 9 ]), which have otherwise been reported as difficult to detect [ 10 ].…”
Section: Introductionmentioning
confidence: 99%